Financial Innovation Strategies to Enhance the Sustainability of MSMEs in the Era of Economic Digitalization - Slamet Pamuji; Deepak R Gupta (PT. Caesarindo Triloka Persada, 2025)
This study examines financial innovation strategies designed to enhance the sustainability of micro, small, and medium enterprises (MSMEs) in the era of economic digitalization. The rapid development of digital technologies such as big data analytics, blockchain, and real-time financial monitoring has transformed the landscape of financial management for entrepreneurs. These innovations provide MSMEs with advanced tools to improve efficiency, optimize decision-making, and respond swiftly to market dynamics. Through digital financial transformation, MSMEs gain broader access to financial information, enabling the formulation of data-driven and adaptive business strategies. However, this transformation also introduces significant challenges, including limited digital literacy, data privacy concerns, cybersecurity risks, and high implementation costs that may hinder widespread adoption among MSMEs. While blockchain technology offers transparency and accountability in financial transactions, its utilization remains minimal due to regulatory uncertainty and cost barriers. The study finds that gradual adoption and context-based implementation of digital financial tools can mitigate risks and support sustainable business growth. To ensure long-term sustainability, MSMEs are encouraged to adopt a phased strategy for financial innovation beginning with automation of basic financial processes and progressing toward integrated digital ecosystems. Ultimately, financial innovation not only strengthens profitability and operational resilience but also fosters transparency, stakeholder trust, and competitiveness. In a broader perspective, it contributes to building a more inclusive, adaptive, and innovation-driven entrepreneurial ecosystem in the digital economy era.